2011
DOI: 10.1155/2011/656013
|View full text |Cite
|
Sign up to set email alerts
|

Neutropenia and Neutropenic Complications in ABVD Chemotherapy for Hodgkin Lymphoma

Abstract: A combination of Adriamycin (a.k.a. Doxorubicin), Bleomycin, Vinblastine, and Dacarbazine (ABVD) is the most commonly used chemotherapy regime for Hodgkin lymphoma. This highly effective treatment is associated with a significant risk of neutropenia. Various strategies are adopted to counter this commonly encountered problem, including dose modification, use of colony stimulating factors, and prophylactic or therapeutic use of antibiotics. Data to support these approaches is somewhat controversial, and in keep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
1
7
0
2
Order By: Relevance
“…For HL, retrospective data suggest that the incidence of FN, neutropenic sepsis, and death in patients receiving ABVD chemotherapy is low ( < 1%) so it can be said that there is no role for routine administration of prophylactic antibiotics. 14 The current study results support this belief for HL patients. However, for all NHL patients even if it is an aggressive type such as DLBCL, TCL and MCL, the current study results conflict with previous findings and recommendations since it can be considered that antimicrobial prophylaxis is not routinely used for these patients.…”
Section: Discussionsupporting
confidence: 82%
“…For HL, retrospective data suggest that the incidence of FN, neutropenic sepsis, and death in patients receiving ABVD chemotherapy is low ( < 1%) so it can be said that there is no role for routine administration of prophylactic antibiotics. 14 The current study results support this belief for HL patients. However, for all NHL patients even if it is an aggressive type such as DLBCL, TCL and MCL, the current study results conflict with previous findings and recommendations since it can be considered that antimicrobial prophylaxis is not routinely used for these patients.…”
Section: Discussionsupporting
confidence: 82%
“…This was a significantly lower rate than that of the NHL cases as was expected from current knowledge. It has been previously reported that neutropenia is a common complication of ABVD chemotherapy, but related complications including febrile neutropenia (FN), neutropenic sepsis, and death are much less frequent [20].…”
Section: Discussionmentioning
confidence: 99%
“…Mounier et al, 2014 showed higher rates of anemia and leukopenia in the BEACOPP 4+4 treatment group vs ABVD [46]. Chemotherapyinduced neutropenia is another common side-effect of HL treatment, and can result in dose-modifications or treatment delays [35,128]. One study reported neutropenia in 90% of patients treated with BEACOPP 4+4 [84].…”
Section: Discussionmentioning
confidence: 99%